Analisis Kesulitan Siswa dalam Memahami Teks Bahasa Arab pada Maharah Qira’ah di Man 5 Jombang - Amanda, Sintia Putri; Maulana Rifqi Naufal Lubis (Bilingua, 2025)
This study analyzes the difficulties experienced by students in understanding Arabic texts in the maharah qirā’ah learning process at MAN 5 Jombang. A descriptive qualitative approach was employed, using observation, interviews, and documentation as data collection techniques, which were then analyzed using the interactive model of Miles and Huberman. The findings reveal two types of difficulties: linguistic and non-linguistic. Linguistic difficulties include limited mastery of vocabulary (mufradāt), weak understanding of sentence structure (nahwu–sharaf), and pronunciation errors that hinder reading fluency. Non-linguistic difficulties involve low learning motivation, negative perceptions of the Arabic language, insufficient learning media, and monotonous teaching methods. These findings highlight the need to improve linguistic competence, enhance learning motivation, and utilize more varied digital learning media to strengthen students’ qirā’ah skills.